The balance of payments – the case of Vietnam - Tran Doan Thanh, Hang; Šíma, Ondřej; Pour, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
This thesis is to concentrate on current account of Vietnam over a decade and twin deficit existence through the same models analysis for current account. The multiple linear regression model is used to investigate the movement of variables (or individual determinant of current account) and modified model is also used to double check and compare the results. Meanwhile, the research also provide comprehensive theories of balance of payment and related theories for topic.
Vedoucí práce: Ondřej Šíma
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses